PENGARUH HARGA, KUALITAS PRODUK DAN PROMOSI TERHADAP BRAND SWITCHING (Studi Pada Konsumen Produk Smartphone Samsung Di DKI Jakarta Yang Berpindah Merek) - Salvariza, Muhammad; Indriani, Farida (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This research aims to analyze the influence of price, product quality, and promotion factors on Brand Switching among consumers of Samsung Smartphones who switch to other brands. The study uses price, product quality, and promotion as independent Variables, and Brand Switching as the Dependent Variable. The sample in this study consists of 97 individuals who are users of Samsung Smartphones and have currently switched to other Smartphone brands, residing in Jakarta. The data for this research were obtained from questionnaires that were processed and analyzed using the SPSS program. The results of this study indicate that price has a positive and significant impact on Brand Switching. The study also shows a positive and significant relationship between product quality and Brand Switching. However, regarding promotion, it was found to have a positive but insignificant effect on Brand Switching.